GENERAL PRINCIPLES OF GOOD GOVERNANCE IN INDONESIA: WHAT ARE THE LEGAL BASES? - Zamroni, M. (Varia Justicia, 2019)
The concept of a welfare state starts from many typical countries, namely the Police State (Polizei Staat), the State of Formal Law (Liberal) and the State of Material Law (Welvaarstaat / welfare state). The Police State and the Welfare State are considered as extreme forms of legal state because the State Police is the beginning of the Law State. Welfare State is a type of legal state that is considered current. The Principles of Good Governance were born during the development of the Welfare State. This study reveals the legal basis of the General Principles of Good Governance of several regulations. The results show that the general principle of good governance is currently regulated comprehensively in regulation in Indonesia. The regulation includes 1) Act Number 28 of 1999 on State Implementation of the Clean and Free from Corruption, Collusion and Nepotism 2) Act Number 9 of 2004, concerning the Amendment to Indonesian Act Number 5 of 1986 on Administrative Courts Country 3) Act Number 25 of 2009 on Public Service 4) Act Number 30 of 2014 concerning Government Administration. As a modern country, general principles of good governance is the spirit for the implementation of the government administration of the Indonesian Republic, especially in the context of the implementation of clean governance based on expediency, justice, and legal certainty.